Clinical Perspectives and Fundamental Aspects of Local Cardiovascular and Renal Renin-Angiotensin Systems - De Mello, Walmor; Frohlich, Edward D. (Frontiers in Endocrinology, 2014)
Evidence for the potential role of organ specific cardiovascular renin-angiotensin systems (RAS) has been demonstrated experimentally and clinically with respect to certain cardiovascular and renal diseases. These findings have been supported by studies involving pharmacological inhibition during ischemic heart disease, myocardial infarction, cardiac failure; hypertension associated with left ventricular (LV) ischemia, myocardial fibrosis and left ventricular hypertrophy (LVH); structural and functional changes of the target organs associated with prolonged dietary salt excess; and intrarenal vascular disease associated with end-stage renal disease (ESRD). Moreover, the severe structural and functional changes induced by these pathological conditions, can be prevented and reversed by agents producing RAS inhibition (even when not necessarily coincident with alterations in arterial pressure).In this review, we discuss specific fundamental and clinical aspects and mechanisms related to the activation or inhibition of local renin angiotensin systems and their implications for cardiovascular and renal diseases. Fundamental aspects involving the role of angiotensins on cardiac and renal functions including the expression of RAS components in the heart and kidney and the controversial role of ACE2 on angiotensin peptide metabolism in humans, were discussed.